Cost-effectiveness of community versus hospital eye service follow-up for patients with quiescent treated age-related macular degeneration alongside the ECHoES randomised trial. Issue 10 (24th October 2016) - Violato, M; Dakin, H; Chakravarthy, U; Reeves, B C; Peto, T; Hogg, R E; Harding, S P; Scott, L J; Taylor, J; Cappel-Porter, H; Mills, N; O'Reilly, D; et al.
Abstract : Objectives: To assess the cost-effectiveness of optometrist-led follow-up monitoring reviews for patients with quiescent neovascular age-related macular degeneration (nAMD) in community settings (including high street opticians) compared with ophthalmologist-led reviews in hospitals. Design: A model-based cost-effectiveness analysis with a 4-week time horizon, based on a 'virtual' non-inferiority randomised trial designed to emulate a parallel group design. Setting: A virtual internet-based clinical assessment, conducted at community optometry practices, and hospital ophthalmology clinics. Participants: Ophthalmologists with experience in the age-related macular degeneration service; fully qualified optometrists not participating in nAMD shared care schemes. Interventions: The participating optometrists and ophthalmologists classified lesions from vignettes and were asked to judge whether any retreatment was required. Vignettes comprised clinical information, colour fundus photographs and optical coherence tomography images. Participants' classifications were validated against experts' classifications (reference standard). Resource use and cost information were attributed to these retreatment decisions. Main outcome measures: Correct classification of whether further treatment is needed, compared with a reference standard. Results: The mean cost per assessment, including the subsequent care pathway, was £411 for optometrists and £397 for ophthalmologists: a cost difference of £13 (95% CI −£18 to £45). Optometrists were non-inferior to ophthalmologists with respect to the overall percentage of lesions correctly assessed (difference −1.0%; 95% CI −4.5% to 2.5%). Conclusions: In the base case analysis, the slightly larger number of incorrect retreatment decisions by optometrists led to marginally and non-significantly higher costs. Sensitivity analyses that reflected different practices across eye hospitals indicate that shared care pathways between optometrists and ophthalmologists can be identified which may reduce demands on scant hospital resources, although in light of the uncertainty around differences in outcome and cost it remains unclear whether the differences between the 2 care pathways are significant in economic terms. Trial registration number: ISRCTN07479761 ; Pre-results.